2024
DOI: 10.11591/edulearn.v18i1.20920
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mathematics module on circle material based on the small group discussion model

Jitu Halomoan Lumbantoruan,
Candra Ditasona

Abstract: This research aims to produce a mathematics module on circle material based on the small group discussion model to improve learning outcomes. The fact is that there are 48% of students who get low mathematics learning outcomes. Another fact is that at the high school level, 62% of students in circle material scored below the minimum completeness criteria. Urgent development research was carried out to produce circular module products. The method in this research is research and development (RD). The subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Based on the results of interviews conducted, the cause of these difficulties was because students were not used to being given questions in the form of stories. According to researchers, teachers should give story questions to students more often in order to add to their learning experience (Dahlström, 2019;Lumbantoruan & Ditasona, 2024). In addition, research conducted by other researchers also found learning difficulties experienced by Grade VII students of Junior high school Luhur Baladika in learning comparative material.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of interviews conducted, the cause of these difficulties was because students were not used to being given questions in the form of stories. According to researchers, teachers should give story questions to students more often in order to add to their learning experience (Dahlström, 2019;Lumbantoruan & Ditasona, 2024). In addition, research conducted by other researchers also found learning difficulties experienced by Grade VII students of Junior high school Luhur Baladika in learning comparative material.…”
Section: Introductionmentioning
confidence: 99%